The Effectiveness of Using Wordwall as Medium to Improve Students’ Writing Skill of Grade VIII - Farisa Fatimatuzzahro; Aprilia Riyana Putri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study investigates the effectiveness of using Wordwall as a learning medium to improve the writing skills of eighth-grade students. Writing is one of the most essential yet challenging skills in English learning, as many students struggle to develop ideas, organize their thoughts, and apply correct grammar and vocabulary. To address this problem, the research employed a pre-experimental design with one group pretest and posttest. The participants were eighth-grade students of MTS Walisongo Pecangaan, selected through purposive sampling. Data were collected using writing tests administered before and after the treatment. The findings show a significant improvement in students’ writing achievement, with the mean score increasing from 53.17 in the pretest to 82.67 in the posttest. The paired sample t-test result indicated a significance value of 0.000 < 0.05, while the N-gain score was 0.71 (71.13%), categorized as high. These results confirm that Wordwall is an effective medium to enhance students’ writing ability and foster better learning outcomes.